Mammary Gland Cell Culture of Macaca fascicularis as a Reservoir for Stem Cells - Silmi Mariya; Fitriya Nur Annisa Dewi; Irma Herawati Suparto; Gregory K. Wilkerson; J. Mark Cline; . Permanawati; Diah Iskandriati; I Nengah Budiarsa; Dondin Sajuthi (Bogor Agricultural University, Indonesia, 2017)
The mammary gland contains adult stem cells that are capable of self-renewal and are likely target for neoplastic transformation leading to breast cancer. In this study, we developed a cell culture derived from the mammary glands of cynomolgus monkeys (Macaca fascicularis)(MfMC) and furthermore identified the expression of markers for stemness and estrogenreceptor-associated activities. We found that the primary culture can be successfully subcultured to at least 3 passages, primarily epithelial-like in morphology, the cultured cells remained heterogenous in phenotype as they expressed epithelial cell markers CD24, CK18, and marker for fibroblast S1004A. Importantly, the cell population also consistently expressed the markers of mammary stem cells (ITGB1 or CD29 and ITGA6 or CD49f), mesenchymal stem cells (CD73 and CD105) and pluripotency (NANOG, OCT4, SOX2). In addition to this, the cells were also positive for Estrogen Receptor (ER), and ER-activated marker Trefoil Factor 1, suggesting an estrogen responsiveness of the culture model. These results indicate that our cell culture model is a reliable model for acquiring a population of cells with mammary stem cell properties and that these cultures may also serve as a reservoir from which more purified populations of stem cell populations can be isolated in the future.